Trichosporon asahii and Trichosporon inkin Biofilms Produce Antifungal-Tolerant Persister Cells - Cordeiro, Rossana de Aguiar; Aguiar, Ana Luiza Ribeiro; da Silva, Bruno Nascimento; Pereira, Lívia Maria Galdino; Portela, Fernando Victor Monteiro; de Camargo, Zoilo Pires; de Lima-Neto, Reginaldo Gonçalves; Castelo-Branco, Débora de Souza Collares Maia; Rocha, Marcos Fábio Gadelha; Sidrim, José Júlio Costa (Frontiers in Cellular and Infection Microbiology, 2021)
Persister cells are metabolically inactive dormant cells that lie within microbial biofilms. They are phenotypic variants highly tolerant to antimicrobials and, therefore, associated with recalcitrant infections. In the present study, we investigated if Trichosporon asahii and T. inkin are able to produce persister cells. Trichosporon spp. are ubiquitous fungi, commonly found as commensals of the human skin and gut microbiota, and have been increasingly reported as agents of fungemia in immunocompromised patients. Biofilms derived from clinical strains of T asahii (n=5) and T. inkin (n=7) were formed in flat-bottomed microtiter plates and incubated at 35°C for 48 h, treated with 100 μg/ml amphotericin B (AMB) and incubated at 35°C for additional 24 h. Biofilms were scraped from the wells and persister cells were assayed for susceptibility to AMB. Additionally, we investigated if these persister cells were able to generate new biofilms and studied their ultrastructure and AMB susceptibility. Persister cells were detected in both T asahii and T. inkin biofilms and showed tolerance to high doses of AMB (up to 256 times higher than the minimum inhibitory concentration). Persister cells were able to generate biofilms, however they presented reduced biomass and metabolic activity, and reduced tolerance to AMB, in comparison to biofilm growth control. The present study describes the occurrence of persister cells in Trichosporon spp. and suggests their role in the reduced AMB susceptibility of T. asahii and T. inkin biofilms.